Safety Test for Ethanolic Neem Leaf (Azadirachta indica A. Juss.) Extract on Male Mice (Mus musculus L) Renal Structure - Ayu Dwi Lestari; Agung Janika Sitasiwi; Sri Isdadiyanto (Faculty of Veterinary Medicine, Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2023)
Neem leaves (Azadirachta indica A. Juss.) are often used as traditional medicine because they contain bioactive compounds such as azadirachtin, nimbidin and nimbolides. Consumption of traditional medicines for long periods can cause side effect on kidney. This study aims to find out the histological structure of glomerular and proximal tubular in the male mice (Mus musculus L.) kidneys after exposure to the ethanolic of neem leaves extract. Completely Randomized Design (CRD) consists of 2 treatment groups with 15 replications was used in this study. The first group is K (only treated with aquadest) and P group (treated by ethanolic neem leaves extrcat at the dosage 14 mg/ kg body weight). The treatment were given orally with a volume of 0.2 mL for 21 days. Feeding and drinking were carried out ad-libitum. At the 22 days, kidney was isolated, weighted and made for histological processed with 5 μm in thickness using paraffin method with Hematoxylin and Eosin staining. The variables observed in this study were kidney weight, water consumption, glomerular diameter, thick of Bowman capsule, diameter of proximal tubule and lumen diameter. Data were analyzed using the t test with a confidence level of 95%. The results of the analysis showed that the treatment has no significant effect (p> 0.05) to kidney weight, water consumption, glomerular diameter, thick of Bowman capsule, diameter of proximal tubules and lumen diameter. The study showed that the use of ethanolic neem leaves extract for 21 days still safe to be use as a traditional medicine.